Differences in wake‐up and unknown onset stroke examined in a stroke registry. Issue 3 (22nd October 2014) - Reid, John M.; Dai, Dingwei; Cheripelli, Bharath; Christian, Christine; Reidy, Yvette; Gubitz, Gord J.; Phillips, Stephen J.
Abstract : Introduction: Debate exists as to whether wake‐up stroke (WUS) (i.e. symptoms first noted on waking) differs from stroke developing while awake [awake onset stroke (AOS)]. Unknown onset stroke (UOS) with unclear symptom onset time is infrequently studied. Aims: This study aimed to examine differences in stroke characteristics and outcomes in these three groups. Methods: The stroke registry database from Halifax Infirmary, Canada, was interrogated for hospitalised stroke patients between 1999–2011. Information was available on demographics, stroke characteristics, and functional status at discharge and six months (modified Rankin score [mRS]). Results: Of 3890 patients, 65% had AOS, 21% WUS and 14% UOS. UOS patients were significantly older, more commonly female and living alone than AOS patients, with no difference between AOS and WUS. UOS rates increased from 10 to 16% of patients during the study period ( P  < 0·0001). UOS but not WUS had a higher stroke severity than AOS. Intracerebral hemorrhage was less common (9 vs. 13%) and lacunar stroke more common (23 vs. 19%) in WUS compared to AOS. In UOS left hemisphere location was more likely, and lacunar stroke less common. Excellent outcomes were slightly lower for WUS. UOS had significantly higher rates of in‐hospital mortality (23 vs. 16%, P  < 0·0001) and poorer functional outcome six months after stroke (mRS < 3 in 26% of UOS and 46% of AOS, P  = 0·02). Conclusion: WUS has lower rates of ICH but similar stroke severity and outcomes to AOS. UOS prevalence appears to be increasing, with higher stroke severity and worse prognosis.